2018
DOI: 10.1111/jora.12458
|View full text |Cite
|
Sign up to set email alerts
|

Differential Susceptibility to Parenting in Adolescent Girls: Moderation by Neural Sensitivity to Social Cues

Abstract: This research examined whether heightened neural activation to social cues confers adjustment advantages in supportive social contexts but adjustment disadvantages in stressful social contexts. Forty-five adolescent girls were exposed to social exclusion during an fMRI scan and reported on parent-child relationship quality and depressive symptoms. Stressful parent-child relationships predicted subsequent depressive symptoms in girls with high and moderate but not low dorsal anterior cingulate cortex, subgenual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 77 publications
2
18
0
Order By: Relevance
“…Thus, rejection sensitivity seems to exert both risk‐augmenting and risk‐protective effects contingent on the social context, such that rejection‐sensitive girls suffer when living in threatening peer environments but benefit when living in favorable peer environments. These results parallel prior research indicating that neural sensitivity to rejection can serve as a differential susceptibility factor, increasing emotional sensitivity to both stressful and supportive family contexts (Rudolph et al, 2020a). These findings therefore add to a growing body of research suggesting that both psychological and biological susceptibilities contribute to context‐dependent developmental outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, rejection sensitivity seems to exert both risk‐augmenting and risk‐protective effects contingent on the social context, such that rejection‐sensitive girls suffer when living in threatening peer environments but benefit when living in favorable peer environments. These results parallel prior research indicating that neural sensitivity to rejection can serve as a differential susceptibility factor, increasing emotional sensitivity to both stressful and supportive family contexts (Rudolph et al, 2020a). These findings therefore add to a growing body of research suggesting that both psychological and biological susceptibilities contribute to context‐dependent developmental outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…However, they did not show higher social competence when in a low chaos environment, so this result might be better explained in a double-risk model although a wider range of structured to chaotic environments might uncover a differential susceptibility cross-over interaction ( Kim-Spoon et al, 2017 ). More direct evidence for differential susceptibility comes from a study in adolescent girls that demonstrated with cross-over interactions that the higher neural activity during social exclusion was associated with an increase in depression in girls with stressful parent-child relationships relative to girls with low neural reactivity, but lower levels of depression in girls with supportive parent-child relationships relative to girls with low neural reactivity ( Rudolph et al, 2020 ). There is almost no research examining the neural development of the medial prefrontal cortex in early childhood, but our model would predict differential susceptibility in two important transition windows in development that are characterized by more rapid neuronal change: infancy/early childhood ( Gilmore et al, 2018 ) and adolescence ( Tamnes et al, 2017 ) ( Fig.…”
Section: Differential Susceptibility To Social Experiencesmentioning
confidence: 99%
“…Initial evidence has observed that aspects of family functioning interact with neurobiological sensitivity to social exclusion by peers to impact internalizing symptoms ( Rudolph et al, 2018 ; Sequeira et al, 2019 ) and externalizing symptoms in adolescent youth ( Schriber et al, 2018 ). Further, in one study of young adults, higher levels of amygdala activation to fearful faces represented a marker of susceptibility to social context (i.e., low socioeconomic resources) in predicting antisocial behavior ( Gard et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%